Water treatment plant design (McGraw-Hill, 1998)
A reference work to the design and construction of water treatment plants. This edition incorporates current EPA standards and developments in the field. New chapters place more emphasis on design, planning, assembly, rehabilitation, operation and maintenance of treatment plant facilities.